Translation and psychometric validation of the Chinese version of the meaningful and enjoyable activities scale for mild dementia - Chen, Hongyu; Wang, Yuanyuan; Zhang, Minyi; Wang, Ning; Hao, Xixi; Xue, Zhihan; Fang, Kui; Liu, Yan (Frontiers in Psychiatry, 2023)
Objectives： To translate 20-item Meaningful and Enjoyable Activities Scale into Chinese and evaluate its psychometric properties amongst Chinese with mild dementia. Methods： A cross-sectional study of 450 people with mild dementia recruited from a memory disorders clinic was conducted with the C-MEAS. Raw data were randomly divided into two parts for exploratory factor analysis and confirmatory factor analysis, to evaluate the construct validity. Content validity and reliability were tested by content validity index and Cronbach's α coefficients, respectively. Results： Adaptation results showed that the Chinese version of the scale is adequate for linguistic and content validation. Confirmatory factor analysis indicated a significantly good fit for a three-factor model. Cronbach's alpha coefficient was 0.84 for the overall scale. Conclusions： The C-MEAS for people with mild dementia is a reliable and valid instrument with satisfactory psychometric properties. Future studies should recruit a more representative sample of people with mild dementia in China to verify the applicability of the scale.